Algunas reflexiones sobre la regulación de la forma contractual en el código civil de 1984 - Ortega-Piana, Marco Antonio (2020)
In the following article, the author will provide an analysis regarding the regulation of the contractual form in the Peruvian Civil Code of 1984, postulating that, in certain key aspects, precisions of the legislative texts are justified.